Agricultural importance, biology, control and utilisation of Cyperus rotundus - Gunasekera, T.G.L.G. (2013)
Purple nutsedge or nutgrass (Cyperus rotundus) is a serious weed species of most of the crops in tropical parts of the world. The agricultural importance of this weed is reviewed. The weed has a well-developed underground system. The biology, economic importance and medicinal properties of purple nutsedge are discussed. Finally, information on different control methods of C. rotundus is summarised